2018
DOI: 10.14196/mjiri.32.107
|View full text |Cite
|
Sign up to set email alerts
|

Impaired nonverbal working memory in high-functioning autism spectrum disorder

Abstract: Background: Past studies have documented working memory impairment in participants with high-functioning Autism Spectrum Disorders (IQ>70), but inconsistent findings have been reported. One possibility is the existence of verbal responses in the evaluation of working memory performance. The aim of the current study is to examine the working memory performance and its correlation with a prominent deficit in participants with high-functioning Autism Spectrum Disorders by non-verbal working memory task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…These changes in synchrony are important not only for understanding the mechanism of the underlying pathology, but also as a potential non-invasive biological diagnostic ( Gandal et al, 2012 ), which may be detectable early in the disease process, and for developing treatments ( Strüber and Herrmann, 2020 ). As a core cognitive function, the impairment of WM appears in many different disorders including schizophrenia ( Park and Holzman, 1992 ; Goldman-Rakic, 1994 ; Roitman et al, 2000 ; Peled et al, 2001 ; Kim et al, 2003 ; Micheloyannis et al, 2006 ; Basar-Eroglu et al, 2007 ; Haenschel et al, 2007 , 2009 ; Badcock et al, 2008 ; Pachou et al, 2008 ; Barr et al, 2010 , 2017 ; Griesmayr et al, 2014 ; Lett et al, 2014 ; Wu et al, 2014 ; Pinal et al, 2015 ; Senkowski and Gallinat, 2015 ; Van Snellenberg et al, 2016 ; Kang et al, 2018 ; Ma et al, 2018 ; Appaji et al, 2020 ; Murphy N. et al, 2020 ), bipolar disorder ( Wu et al, 2014 ; Appaji et al, 2020 ), autism spectrum disorder ( Bangel et al, 2014 ; Rabiee et al, 2018 ), Parkinson’s disease ( Siegert et al, 2008 ; Cools and D’Esposito, 2011 ; Zhao et al, 2018 ; Harrington et al, 2020 ), psychosis ( Gold et al, 2019 ), Attention-deficit/hyperactivity disorder (ADHD; Martinussen et al, 2005 ; Wolf et al, 2009 ; Matt Alderson et al, 2013 ; Bédard et al, 2014 ; Wu et al, 2017 ; Zammit et al, 2018 ; Jang et al, 2020 ), and depression ( Shan et al, 2018 ). The role of synchronized oscillations in different brain disorders has been thoroughly examined elsewhere ( Uhlhaas and Singer, 2006 ), and there is much recent interest in identifying non-invasive and quantitative signatures for different disorders ( Başar, 2013 ; Nimmrich et al, 2015 ; Asllani et al, 2018 ).…”
Section: Dysfunctions In Oscillations and Synchrony During Working Memory Occur In Brain Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in synchrony are important not only for understanding the mechanism of the underlying pathology, but also as a potential non-invasive biological diagnostic ( Gandal et al, 2012 ), which may be detectable early in the disease process, and for developing treatments ( Strüber and Herrmann, 2020 ). As a core cognitive function, the impairment of WM appears in many different disorders including schizophrenia ( Park and Holzman, 1992 ; Goldman-Rakic, 1994 ; Roitman et al, 2000 ; Peled et al, 2001 ; Kim et al, 2003 ; Micheloyannis et al, 2006 ; Basar-Eroglu et al, 2007 ; Haenschel et al, 2007 , 2009 ; Badcock et al, 2008 ; Pachou et al, 2008 ; Barr et al, 2010 , 2017 ; Griesmayr et al, 2014 ; Lett et al, 2014 ; Wu et al, 2014 ; Pinal et al, 2015 ; Senkowski and Gallinat, 2015 ; Van Snellenberg et al, 2016 ; Kang et al, 2018 ; Ma et al, 2018 ; Appaji et al, 2020 ; Murphy N. et al, 2020 ), bipolar disorder ( Wu et al, 2014 ; Appaji et al, 2020 ), autism spectrum disorder ( Bangel et al, 2014 ; Rabiee et al, 2018 ), Parkinson’s disease ( Siegert et al, 2008 ; Cools and D’Esposito, 2011 ; Zhao et al, 2018 ; Harrington et al, 2020 ), psychosis ( Gold et al, 2019 ), Attention-deficit/hyperactivity disorder (ADHD; Martinussen et al, 2005 ; Wolf et al, 2009 ; Matt Alderson et al, 2013 ; Bédard et al, 2014 ; Wu et al, 2017 ; Zammit et al, 2018 ; Jang et al, 2020 ), and depression ( Shan et al, 2018 ). The role of synchronized oscillations in different brain disorders has been thoroughly examined elsewhere ( Uhlhaas and Singer, 2006 ), and there is much recent interest in identifying non-invasive and quantitative signatures for different disorders ( Başar, 2013 ; Nimmrich et al, 2015 ; Asllani et al, 2018 ).…”
Section: Dysfunctions In Oscillations and Synchrony During Working Memory Occur In Brain Disordersmentioning
confidence: 99%
“…These changes in synchrony are important not only for understanding the mechanism of the underlying pathology, but also as a potential non-invasive biological diagnostic (Gandal et al, 2012), which may be detectable early in the disease process, and for developing treatments (Strüber and Herrmann, 2020). As a core cognitive function, the impairment of WM appears in many different disorders including schizophrenia (Park and Holzman, 1992;Goldman-Rakic, 1994;Roitman et al, 2000;Peled et al, 2001;Kim et al, 2003;Micheloyannis et al, 2006;Basar-Eroglu et al, 2007;Haenschel et al, 2007Haenschel et al, , 2009Badcock et al, 2008;Pachou et al, 2008;Barr et al, 2010Barr et al, , 2017Griesmayr et al, 2014;Lett et al, 2014;Wu et al, 2014;Pinal et al, 2015;Senkowski and Gallinat, 2015;Van Snellenberg et al, 2016;Kang et al, 2018;Ma et al, 2018;Appaji et al, 2020;, bipolar disorder (Wu et al, 2014;Appaji et al, 2020), autism spectrum disorder (Bangel et al, 2014;Rabiee et al, 2018), Parkinson's disease (Siegert et al, 2008;Cools and D'Esposito, 2011;Zhao et al, 2018;Harrington et al, 2020), psychosis (Gold et al, 2019), Attentiondeficit/hyperactivity disorder (ADHD; Martinussen et al, 2005;Wolf et al, 2009;…”
Section: Dysfunctions In Oscillations and Synchrony During Working Me...mentioning
confidence: 99%
“…While each of these NDDS has some unique behavioral features, they can also share behavioral impairments, such as alterations in social functioning, impulsivity, and executive function deficits [29,[334][335][336][337][338][339][340][341][342][343][344][345][346][347][348][349]. Cognitive/executive function deficits are also common in NDGDS (AD [350,351], PD [352,353], MS [354][355][356][357], ALS [358][359][360][361][362]), as are alterations in social behaviors [363][364][365] and manifestations of impulsive-like behaviors [366][367][368][369][370].…”
Section: Shared Features Of Neurodevelopmental Disorders and Neurodeg...mentioning
confidence: 99%
“…Meta-cognitive skills such as working memory and planning have been shown to predict social skills in autistic but not NT children ( Leung et al, 2016 ). Behavioral research investigating spatial, verbal, and nonverbal working memory in autistic individuals has shown functional challenges, including reduced accuracy and slower performance (for a meta -analysis, see: Wang et al, 2017 , Rabiee et al, 2018 , Sachse et al, 2013 , Cui et al, 2010 ). Conflicting research, however, has shown intact verbal working memory as measured by n -back letter tasks ( Williams et al, 2005 ) and intact visual working memory as measured by a visual change detection task ( Lynn et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%